Fingolimod and Diabetic Retinopathy: A Drug Repurposing Study - Gesualdo, Carlo; Balta, Cornel; Platania, Chiara Bianca Maria; Trotta, Maria Consiglia; Herman, Hildegard; Gharbia, Sami; Rosu, Marcel; Petrillo, Francesco; Giunta, Salvatore; Della Corte, Alberto; Grieco, Paolo; Bellavita, Rosa; et al. (Frontiers in Pharmacology, 2021)
This study aimed to investigate the interactions between fingolimod, a sphingosine 1-phosphate receptor (S1PR) agonist, and melanocortin receptors 1 and 5 (MCR1, MCR5). In particular, we investigated the effects of fingolimod, a drug approved to treat relapsing-remitting multiple sclerosis, on retinal angiogenesis in a mouse model of diabetic retinopathy (DR). We showed, by a molecular modeling approach, that fingolimod can bind with good-predicted affinity to MC1R and MC5R. Thereafter, we investigated the fingolimod actions on retinal MC1Rs/MC5Rs in C57BL/6J mice. Diabetes was induced in C57BL/6J mice, through streptozotocin injection. Diabetic and control C57BL/6J mice received fingolimod, by oral route, for 12 weeks and a monthly intravitreally injection of MC1R antagonist (AGRP), MC5R antagonist (PG20N) and the selective S1PR1 antagonist (Ex 26). Diabetic animals treated with fingolimod showed a decrease of retinal vascular endothelial grow factor A (VEGFA), vascular endothelial growth factor receptor 1 and 2 (VEGFR1 and VEGFR2) compared to diabetic control group. Fingolimod co-treatment with MC1R and MC5R selective antagonists, significantly (p<0.05) increased retinal VEGFR1, VEGFR2 and VEGFA levels compared to mice treated with fingolimod alone. Diabetic animals treated with fingolimod plus Ex 26 (S1PR1 selective blocker) had VEGFR1, VEGFR2 and VEGFA levels between diabetic mice group and the group of diabetic mice treated with fingolimod alone. This vascular protective effect of fingolimod through MC1R and MC5R was evidenced also by fluorescein angiography in mice. Finally, molecular dynamic simulations showed a strong similarity between fingolimod and MC1R agonist BMS-470539. In conclusion, the anti-angiogenic activity exerted by fingolimod in DR seems to be mediated not only through S1P1R, but also by melanocortin receptors.